Twerking, Alcohol, Ordination: Rethinking Sacred and Secular with Rot Hae’s Mobile and Participatory Performances in Thailand - Wisuttipat, Nattapol (MUSICultures, 2025)
This article examines the mobile and participatory aspects of rot hae รถ แห่, a musical performance on a moving vehicle, such as a truck or a cart. Despite its popularity, rot hae is criticized for instigating alcohol consumption and sexually provocative dance moves in public, particularly during Buddhist ordination parades. I argue that the mobility and participatory nature of rot hae performances allows it to challenge the established social order and their participants to seek otherwise prohibited sensual pleasures. Such encounters reveal the vernacular practices of Buddhism that cannot be easily mapped onto the sacred-secular dichotomy.